Translation of talk test responses to exercise training in a clinical population - Lyon, Ellen J. (My University, 2013)
The Talk Test (TT) is a submaximal, incremental exercise test that has been shown to be useful in prescribing exercise. It is based on a subject's ability to speak comfortably during exercise. This study defined the amount of reduction in absolute workload intensity determined from an incremental exercise test appropriate for cardiac rehabilitation patients. Patients (N=16) performed an incremental exercise test, with the TT given every 2-minute stage. Patients rated their speech comfort after reciting a standardized paragraph. Anything other than a ?yes? response was considered the ?equivocal? stage, while all preceding stages being ?positive? stages. Subsequently, three 20-minute steady-state training bouts were performed in random order at the absolute workload associated with the Last Positive (LP), LP-1, and LP-2 stages of the incremental test. Speech comfort, heart rate (HR), and Rating of Perceived Exertion (RPE) were recorded every 5 minutes. The 20-minute exercise training bout was completed fully by: LP (N=11), LP-1 (N=15), LP-2 (N=16). The results were based on the most appropriate speech comfort responses, HRs, and RPEs seen in each steady-state bout. It was determined that prescribing exercise at intensity associated with the LP-1 stage of the TT is most suitable for a clinical population.
Keywords: Exercise tests.; Exercise.; Treadmill exercise tests--Physiological aspects.